Preparation of Epidermal Tissues for Light Microscope Studies of Vitis - leaves - Swanepoel, J.J.; De La Harpe, A. C. (South African Journal of Enology and Viticulture, 2017)
A method for preparing epidermal tissues of leaves of Vitis spp. for the study of surface characteristics with the aid of a light microscope is described. Certain morphological characteristics such as trichrome length and frequency, stomata frequency, diameter and index of two cultivars were determined by means of a light microscope which compared very favourably with the results obtained when using a scanning electron microscope.